OUTDOOR LEARNING EFFECTIVITY IN ENHANCHING HIGH SCHOOL STUDENT’S ECOLOGICAL LITERACY - Achmad Mashfufi; Heribertus Soegiyanto; Puguh Karyanto (Universitas Sebelas Maret (UNS), 2018)
The aims of this thesis writing are: (1) to know the equipment characteristic of SSP based outdoor learning model CTL on living environment subject for XI grade of SMA (2) To know the expedient equipment of SSP based Outdoor Learning Model CTL on living environment subject for XI grade of SMA (3) to know the equipment effectively of Subject Specific Pedagogy (SSP) based outdoor learning model CTL on living environment subject for XI grade of SMA. This research was Research and Development. R & D stage used 4D development model. This research was only focused on 3-D stage (Define, Design, and Develop). The disseminate stage was not done because the research aim was only reached the stage of product development. The effectiveness test used pre test – post test of learning outcome and ecological literacy reinforcement in experiment and control class and used N-Gain analysis and T-test. Based on the data analysis, the research result can be presented as follows: (1) the characteristic of SSP based Outdoor Learning by inserting seven components of CTL and insert of NEP dimension consisted of limits to growth, balance of nature, anti-anthropocentrism, and eco-crisis dimension. (2) Validating result from team expert showed the average assessment of RPP was 78%, including very fair criteria; the average assessment of module was 81%, including very fair criteria; the average assessment of LKS was 81%, including very fair criteria; the average assessment of instrument was 83%, including very fair criteria. (3) The effectiveness count showed an improvement of pre-test to post-test score was 0,538, while improvement in control class was only 0,392, so it can be concluded that experiment class used SSP based outdoor learning model CTL in learning process more effective that control class.